The variability of meteoroid falling. (15th October 2016) - Velasco Herrera, V.M.; Cordero, G.
Abstract: We analysed a historical catalogue of meteoroid falling during the last 400 years. We report here for the first time the synchronization between observed meteors and solar barycentric parameters in 19.6 and 13.2 years periodicities using a new multiple cross wavelet. The group of moderated number of meteors is distributed around the positive phase of the solar barycentric periodicity of 13.2 years. While the group of severe number of meteors are distributed on the positive phase of the solar barycentric periodicity of 19.6 years. These periodicities could be associated with Jupiter periodicities. So understanding the modulation of meteoroid falling is important for determining the falling patterns of these objects and for knowing when it is more likely to expect the entry of one of these objects into the Earth's atmosphere, because bodies falling onto the Earth can cause damage from minor impacts to mass-extinctions events. One of the most extreme events was the formation of the Chicxulub impact crater 65, 000, 000 years ago that caused one of the five major mass extinctions in the last 500, 000, 000 years. During the 20th and 21st centuries, a series of events demonstrated the importance of collisions between planets and small bodies (comets and asteroids), which included our own planet. In the case of the Earth, we can cite three examples: Tunguska, Curuça and Chelyabinsk. These events invite us to think that perhaps the occurrence of this phenomenon might be more common than we realize, but the lack of communication or people in the area where they happened prevents us from having a complete record. Modern man has not witnessed the impact of large asteroids or comets on our planet, but it has been observed on other planetary bodies. The most spectacular of these events was the collision of fragments of the comet Shoemaker–Levy 9 with Jupiter in 1994. The total energy of the 21 impacts on Jupiter's atmosphere was estimated as the equivalent of tens of millions of megatons of TNT. Abstract : Highlights: We analysed a historical catalogue of meteoroid falling during the last 400 years. We found synchronization between observed meteors and solar barycentric parameters on decadal time-scales. Multiple cross wavelet analysis identifies periodicities at 19 years and 13 years These periodicities could be associated with Jupiter periodicities.